Technology Transfer Obstacles - Mohd Ghazali, Maarof; Sorooshian, Shahryar; Syed Radzi, Rahamaddulla; Suhaila, Abdul Hamid (IJPT, 2017)
This paper identifies the potential barriers that can affect effective collaboration between industry and public universities of Malaysia. Intense global competition has created new requirements to the industry: constant new technological breakthrough, rapid deployment of new technological solutions and shorter product life-cycle. Thus, both the industry and the university need to look into possibilities of sharing knowledge-based capital, technological facilities and access to new scientific development and innovation. Data for this study was obtained through interviews with top management of companies which have experience in collaboration with Malaysian public universities. Later, the data was analyzed using thematic analysis. Among the barriers identified were products are not market driven, bureaucracy, insufficient experience on applied research, lack of proper standard operating procedures, unattractive reward system, lack of information on potential collaboration opportunities and Intellectual Property issues